ADSORPTION METHOD FOR ISOLATING IONS OF SOME HEAVY METALS AND PETROLEUM PRODUCTS - A. A. Ismailov; A. M. Mamatov; Sh. P. Nurullaev; Sh. N. Ataullaeva (Galaxy International Interdisciplinary Research Journal, 2024)
The work investigated the physicochemical properties of wastewater treatment (WT) from heavy metal ions (HMI) and petroleum products (PP) using composite sorption materials (CSM), obtained from rotary slag waste from a battery plant and wood fiber waste from the city of Jizzakh, Republic of Uzbekistan. It is shown that the HMI adsorption isotherms correspond to a monomolecular layer with the participation of micro- and macropores, and it is also found that the adsorption isotherms are described by the Langmuir class of polymolecular adsorption. It was found that the efficiency of wastewater treatment from petroleum products is 90-99.6%. CSM was restored by thermal regeneration at a temperature that represents the treatment of the sorbent with steam or gases at 110°-400℃.